(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Like many of Greene’s characters, Greene lived in a state of psychological and emotional extremity. He was forever marked by an experience of psychoanalysis as a teenager and contemplated suicide as a young man. Haunted by a sense of sin and a constant anxiety, Greene’s nearly incessant world travel. Like the author himself, the characters often took to make deals with God that will leave them free to pursue their own passion. We find that in each of his novel, corruption is the path to salvation or at least to recovery to the soul. Characters become involved with the dirt and sweat of existence and in doing so find that it can be made holy. The hard drinking, adulterous priest in The Power and The Glory is a prime example of this sinner-who-might-be-a-saint He is neither noble nor particularly faithful, but in administering the sacraments at the risk of his own life, he becomes a flawed instrument of divine grace.